The influence of change in business environment on change in the adoption and use of managementcontrol system: a study of Libyan small and medium size privatized firms pre and post-privatization / Yosef Kalefa Hosen - Hosen, Yosef Kalefa (Institute of Graduate Studies, UiTM, 2013)
This study utilizes the contingency theory approach to investigate the contingent relationships between change of several contextual factors (intensity of competition, business strategy, information technology and national culture) and change in adoption and use of management control systems (MCS) among small and mediumsize firms during the pre and post-privatization periods in the Libyan context. It also investigates the relationship between change in adoption and use of MCS and change in firm performance. This study also seeks to develop a wider and more comprehensive view of adoption and use of MCS among small and medium size firms. This study fills the gap between theory and practices of MCS by testing the change in adoption and use of MCS over time, pre and post-privatization. To achieve the objectives, the study employed the mixed method. First, quantitative data were collected through a survey during which 178 managers (81% response rate) answered a questionnaire. Next, qualitative data were obtained from 19 managers in two case studies for insights into how and why MCS has changed…